Quo Vadis Authority to Manage Public Agency Credits by The State Credits Affairs Committee (PUPN) - Indrawati, Yuli (JURNAL USM LAW REVIEW, 2024)
This study aims to examine the authority of the State Credits Affairs Committee (PUPN) to settle public agency credit. The Constitutional Court (MK) Decision Nr. 77/PUU-IX/2011 which abolished the phrase settlement of credits from bodies that are either directly or indirectly controlled by the State by PUPN. Otherwise, Government Regulation No. 28 of 2022 concerning Pengurusan Piutang Negara oleh PUPN regulated that PUPN can handle creditors in bad faith from special bodies/institutions/public legal entities. The research questions how public agency credits are managed by PUPN? This study differs from previous studies because it uses a public financial law perspective on the characteristics of public bodies as sui generis institutions and PUPN’s special authority in managing receivables. This research is important because it provides a legal study on legal certainty in the practice of managing public agency receivables by PUPN and eliminates concerns about lawsuits over the management of said receivables by PUPN. The research results show that processing public agency receivables by PUPN is only an alternative determined by the public agency - it does not have to be submitted. This concept is based on the application of the sui generis nature and legal subject status of public bodies and is used to optimize the management of public bodies' credits because PUPN has extraordinary coercive authority. This kind of mechanism has a positive value for public bodies in maintaining their financial health and also in efforts to maintain optimal service to the public which is the task of public bodies.